Geologic reconnaissance map of the northwestern part of Seward Peninsula / U.S. Geological Survey; topography by T.G. Gerdine, D.C. Witherspoon and Alfred H. Brooks - Geological Survey (U.S.) (Washington, D.C. : Geological Survey (U.S.), 1907)
Relief shown by contours and spot heights. "U.S. Geological Survey bulletin no. 328, pl. xi." Color 1:250,000